Protein Profile of Fresh Cheese with Lime Juice as Acidifier (Jurnal Ilmu dan Teknologi Hasil Ternak, 2007)
A researh about the making of fresh cheese used lime juice as an acidifier compared to citric acid has been done. The research was aimed to learn the potency of lime juice as acidifier in the making fresh cheese and to know about its protein profile. The experiment was designed by completely randomized design. Those treatments were : A1 = the use of lime juice 0.5 % (v/v), A2 = the use of citric acid 0.05 % (w/v) and A3 = the use of 0.25 % lime juice + citric acid 0,025 %. Variation of those acidification treatment didn’t show any defference on protein profile of fresh cheese, which showed by 8 benz of three treatment with have molecule wheight 17.14; 20.51; 27.92; 36.22; 44.05; 50.11; 53.45, and 102.32 Kda, respectively. The result of the using lime juice, citric acid, and both combination relatively proved same profile. Keywords : protein profile, fresh cheese, lime juice, acidifier